“Too Much, Too Little, Too Late:” Exploring the Role of the Criminal Justice System Within the Narratives of Men Convicted of Sexual Recidivism in Norway and North America - Sandbukt, Ingeborg Jenssen (Sexual offending, 2025)
We present a targeted comparative analysis of two international samples of men incarcerated for sexual recidivism. A total of 30 men were interviewed: 16 from Norway and 14 from North America. The two jurisdictions from which these men were drawn represent the opposite ends of a global continuum of approaches to justice and punishment. We follow Rimer and Holt’s (2023) methodological approach and examine comparatively the way participants described their lived experience of custody, community release, and subsequent reoffending. Although all participants were convicted of crimes that carry the heaviest social stigma, the legislation and structural stigma to which they were subject were distinct. Many participants in both groups attributed their reoffending (at least in part) to systemic inadequacies of the criminal justice regime to which they were exposed. We discuss how these perceived inadequate responses of both countries appear in recidivism narratives in turn. First, we juxtapose the North American system (which was described as “too harsh”) with the comparatively relaxed Norwegian system (which was “too soft”). Second, we consider how treatment was offered (or mandated) in both jurisdictions and describe how there appears to be “no way out” of treatment for the North American men, and yet no way “into” treatment for the Norwegian men. Finally, we compare the men’s perspectives of being “set up to fail” with “too many hoops” in North America and “no safety net” in Norway. The relevance of their narratives for informing best practices is described and general policy implications within a framework of quaternary prevention are discussed.